Modification of histone 3 lysine 27 (H3K27) trimethylation in EZH2 and JMJD3 deficient T cells attenuates atherosclerosis through polarization towards anti-inflammatory phenotypes. (25th November 2020) - Lacy, M; Nitz, K; Janjic, A; Wu, Y; Venkatasubramani, A; Imhof, A; Enard, W; Weber, C; De Winther, M; Atzler, D; Lutgens, E
Abstract: Background: The trimethylation status of Histone 3 Lysine 27 (H3K27), which is regulated by the methylating enzyme Enchancer of zeste homolog 2 (EZH2) and the demethylating enzyme Jumonji domain containing 3 (JMJD3), is a critical epigenetic signature for the differentiation and polarization of T cells. During atherogenesis, T cells initiate and propagate lesion formation through imbalanced polarization of T helper (Th) cells leading to the accumulation of pro-atherogenic T cell subsets, including Th1, that exacerbate inflammation. Purpose: We hypothesize that T-cell EZH2 and JMJD3 may contribute to inflammation and atherosclerotic plaque formation through opposing polarization of T helper cells. Methods: We generated transgenic mice with either Ezh2 or Jmjd3 flanked by loxP-sites that were sensitive to Cre-mediated inactivation. Mice were backcrossed to apolipoprotein E (ApoE−/−) mice expressing Cre in T cells (Cd4Cretg) to generate hypercholesterolemic Ezh2fl/fl-Cd4Cre-ApoE−/− (Ezh2fl/fl) and Jmjd3fl/fl-Cd4Cre-ApoE−/− (Jmjd3fl/fl) mice. Following a 6 week high fat diet, the immune status and atherosclerotic progression of the mice were assessed by histology, flow cytometry, and RNA sequencing. Results: Mass spectrometry of histones isolated from CD4+ T cells confirmed a decrease in H3K27 trimethylation in Ezh2fl/fl mice and an increase in Jmjd3fl/fl mice (p=0.0002 and p=0.01, respectively). In the aortic root, both Ezh2fl/fl and Jmjd3fl/fl mice developed significantly less atherosclerosis (p=0.001 and p=0.0006, respectively). A shift from naive T cells to effectors was observed in the lymph nodes and spleens in both models (p<0.0001 for all). Flow cytometric analysis revealed a systemic accumulation of Th2 in Ezh2fl/flmice (p<0.0001), which was corroborated by a 2.75 log2 fold change of IL-4 expression (padj<0.0001) (RNA-sequencing) in CD4+ T cells as well as elevated IL-4 plasma concentrations (p=0.04). Ingenuity pathway analysis revealed the canonical Th1 pathway was inhibited in Ezh2fl/fl mice. In Jmjd3fl/fl mice, flow cytometric analysis revealed a 2 fold increase of Foxp3-expressing T regulatory (Treg) cells in the blood (p=0.005), lymph nodes (p<0.0001), and spleen (p<0.0001). Conclusions: Our data demonstrate deficiency of either EZH2 or JMJD3 strongly reduce lesion progression in atherosclerosis through polarization of T cells towards anti-atherogenic Th2 or Treg populations, respectively. Targeting T-cell H3K27 trimethylation may be a promising candidate for further investigation to treat atherosclerosis. Funding Acknowledgement: Type of funding source: Public grant(s) – National budget only. Main funding source(s): German Research Foundation (DFG)